Prevalence and characteristics of e-cigarette use among adults in Malaysia - Ab Rahman, Jamalludin; Nik Mohamed, Mohamad Haniki; Mohd Yusoff, Muhammad Fadhli; Ab Rahman, Norny Syafinaz; Draman, Samsul; Kartiwi, Mira; Mahadir Naidu, Balkish; Aris, Tahir (EU European Publishing, 2018)
Background: E-cigarette (e-cig) use has become a worldwide phenomenon since 2010. This study aims to determine the prevalence of e-cig use, distribution and characteristics among Malaysian adults. Malaysia is a typical Asian country. The results of this study will provide evidence for policy makers to formulate appropriate measures towards regulation of e-cig in Malaysia and can become a reference for other similar countries. Methods: Complex sampling design was used to represent 19 million of Malaysian adult household. Samples were stratified by states and urbanity. Sampling units were districts, enumeration blocks and living quarters. All adults from the selected houses were invited to participate in this survey. Analysis was done using sampling weight and complex sampling analysis. Characteristics of current e-cig users were described unweighted. Results: A total of 4,288 individual responded in this survey. Majority of the respondents were at 25-44 years of age group (44%), Malay ethnicity (73%), completed at least secondary level of education (69%), working in private sectors (26%), Muslim (79%) and married (68%). Male and female were equally represented. Based on weighted population, 72% of the respondents were from the urban residential area. The prevalence of current e-cig users in Malaysia was 3.2% (95%CI 2.5-4.1), involving an estimated population of about 600,000 household residence. The prevalence in urban and rural were 3.3 (95%CI 2.4-4.4) and 2.8% (95%CI 2.1-3.8) respectively. E-cig users were common among young, male, Malay, highly educated, Muslim, single and those in urban area. Most of current e-cig users started smoking e-cig when they were 19 years and above. 48% used e-cig just to try, while 17% used it to quit cigarette smoking. 62% preferred nicotine in their e-cig liquid. Conclusions: This study able to represent adults Malaysians and results can be used to guide healthcare managers to manage e-cigarette use countries with similar characteristics.